A research into difference in effective attacks by physical attributes in soccer - Higuchi, T.; Horino, H. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The physical attributes relate the decision of tactics of a team in soccer. However, the research that refers to the relation between players` physical attributes and tactics has not been found. Therefore, the aim of this study is to research into difference in effective attacks by players` physical attributes for the attack scenes in specific top-level matches. Methods All the 29 matches that were in the knockout phase of UEFA Champions League 2008-09 were analyzed. Those teams were classified as the teams in Spain (S group) or the teams in other countries (O group). The video analysis was conducted about "the number of passes", "the attacking time", "the attacking pattern" and "the last pass". The statistical methods were employed by using unpaired t-test for "the number of passes" and "the attacking time", and the Chi-square test for "the attack pattern" and "the last pass". Results & Discussion Seeing Figure 1, S group attacked significantly more passes and took more time than O group (p<0.05). And, S group was significantly higher as "set offence" and "short pass", meanwhile, O group as "fast break", "long pass", and "no passing" (p<0.05). Therefore, it has been suggested that S group had adopted attacks which were more skillful and using more effective mobility, whereas O group had played more powerful and speedily. According to Yamanaka (1999), skill, tactical, and physical levels of players influence the decision of tactics of the team. The result of the report agreed to this research. Conclusion It has been suggested that there is the difference in attacking tactics by players` physical attributes.